The influence of graphene oxide nanosheets on concrete properties on micro level - Nyamsuren, Anudari; Anudari Nyamsuren (České vysoké učení technické v Praze, 2022)
The thesis investigates the effects of graphene oxide (GO) as an additive in cementitious materials. This research aims to assess the benefits of employing graphene oxide as a reinforcement material on a nanoscale and primarily investigates how graphene oxide affects the microstructure of concrete. Although concrete is a fantastic material in compression, it is brittle and has low tensile and flexural strengths. Therefore, in the concrete research community, novel materials, particularly nanomaterials, capable of strengthening concrete and improving its properties on a nanoscale are of great interest. Graphene oxide nanosheets have demonstrated excellent qualities and promising outcomes in enhancing concrete's mechanical properties and microstructure. The first part of the thesis focuses on the literature review and previous discoveries in graphite-based materials. Then, studies about integrating graphene oxide into concrete materials and numerous previous test results are covered. The final section of this thesis focuses on experimental work. The impact of GO nanosheets on the microstructure of concrete samples containing GO at 0% and 0.03% by weight of cement and cured for 21 days will be thoroughly examined using a nanoindentation test and SEM analysis. In addition, the experiment will investigate the mechanical parameters such as tensile strength and compressive strength of concrete samples cured for 28 days.

The thesis investigates the effects of graphene oxide (GO) as an additive in cementitious materials. This research aims to assess the benefits of employing graphene oxide as a reinforcement material on a nanoscale and primarily investigates how graphene oxide affects the microstructure of concrete. Although concrete is a fantastic material in compression, it is brittle and has low tensile and flexural strengths. Therefore, in the concrete research community, novel materials, particularly nanomaterials, capable of strengthening concrete and improving its properties on a nanoscale are of great interest. Graphene oxide nanosheets have demonstrated excellent qualities and promising outcomes in enhancing concrete's mechanical properties and microstructure. The first part of the thesis focuses on the literature review and previous discoveries in graphite-based materials. Then, studies about integrating graphene oxide into concrete materials and numerous previous test results are covered. The final section of this thesis focuses on experimental work. The impact of GO nanosheets on the microstructure of concrete samples containing GO at 0% and 0.03% by weight of cement and cured for 21 days will be thoroughly examined using a nanoindentation test and SEM analysis. In addition, the experiment will investigate the mechanical parameters such as tensile strength and compressive strength of concrete samples cured for 28 days.
The influence of graphene oxide nanosheets on concrete properties on micro level
Keywords: graphene oxide; nanosheets; nanomaterials; nano-reinforcement; concrete reinforcement; concrete additives; graphene oxide; nanosheets; nanomaterials; nano-reinforcement; concrete reinforcement; concrete additives